The virtual learning environment for Ibec Global Graduates 1 - Hennigan, Rowena (Henry Stewart Talks, 2019)
Irish Business and Employers Confederation, Ibec Global Graduates (IGG), Distance learning, VLE, TU Dublin webcourses, Videos, ebooks & webinars, Discussion boards & feedback